Improving the labour market integration and well-being of young adults in times of crisis - Carla Hornberg (INVEST Research Flagship Centre, University of Turku, 2024)
Improving the labour market prospects of young adults is a major concern in European countries. From a life-course perspective, young people's entry into the labour market, especially into rewarding jobs, is crucial for promoting positive career trajectories. Research has widely demonstrated that this phase strongly influences subsequent career paths and success in other life domains, such as family formation. This policy brief summarises key findings on the prevalence and drivers of outcomes for young adults, highlighting both similarities and differences across four broad outcome domains. The most influential explanatory factors are highlighted in order to identify promising pathways for ensuring young adults' labour market integration and well-being.
Keywords: 330